2013
DOI: 10.1007/s12040-013-0270-6
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation coefficient trends in the recent decades over four major Indian metropolitan cities

Abstract: Indian metros, viz., Mumbai, Delhi, Kolkata and Chennai is analysed to study the trends and long term variations in ventilation coefficients and the consequences on the air quality due to these variations in the four metros. A decreasing trend in ventilation coefficient is observed in all the four metros during the 30 years period indicating increasing pollution potential and a degradation in the air quality over these urban centers. In Delhi, the ventilation coefficient decreased at the rate of 49 and 32 m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The mixing height was observed to vary diurnally, with comparatively low mixing height in the night and morning (Mehta et al 2016). It was also reported that the reason for the occurrence of high pollution potential was due to low mixing height (less than 500 m) and mean wind speed less than 4 m/sec during the morning hours (Gross 1970;Iyer and Raj 2013). Thus, morning hours with high traffic flow and less wind speed can result into poor air quality.…”
Section: Effect Of Meteorologymentioning
confidence: 99%
“…The mixing height was observed to vary diurnally, with comparatively low mixing height in the night and morning (Mehta et al 2016). It was also reported that the reason for the occurrence of high pollution potential was due to low mixing height (less than 500 m) and mean wind speed less than 4 m/sec during the morning hours (Gross 1970;Iyer and Raj 2013). Thus, morning hours with high traffic flow and less wind speed can result into poor air quality.…”
Section: Effect Of Meteorologymentioning
confidence: 99%
“…The percentage gradually decreases with an increase in mixing ratio range and reduces to a value of~1 % at mixing ratios greater than 600 ppbv. Further, a breakup of distribution of upto 100 ppbv is also provided in the Ventilation coefficient is used to determine the air quality and pollution potential of a region (Iyer and Raj 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Convective ABL height is referred to the height where the potential temperature begins to increase and stable ABL height is designated as the height where the first important vertical potential temperature gradient variation takes place [35]. Ventilation index (VI) provides information about the ventilation ability of the ABL [28,29]. The equation for the ventilation index following Pasch et al [36] is as follows: Diagrams for stable energy.…”
Section: Calculation Of Blsimentioning
confidence: 99%
“…Likewise, both the CAPE and the E W parameter consider the ability of the boundary layer (BL) atmosphere to diffuse air pollutants from a thermodynamic point of view but does not consider the horizontal removal ability of wind speed. Therefore, many authors have alternatively used the pollution coefficient P i [26,27] and ventilation index (VI) [28,29] to study the relationship between pollution and wind. However, both P i and VI consider the ability of the boundary layer atmosphere to diffuse air pollutants from a kinetic point of view and do not consider the vertical diffusion capacity of the BL.…”
Section: Introductionmentioning
confidence: 99%